Writing matters a handbook for writing and research - Howard, Rebecca Moore (McGraw-Hill Education, 2019)
"Writing Matters unites research, reasoning, documentation, grammar and style in a cohesive whole, helping students see the conventions of writing as a network of responsibilities writers have to other writers."-- Provided by publisher